El juego trabajo y las habilidades cognitivas en los niños de 3 y 4 años de la Unidad Educativa “Fernando Suárez Palacio” período 2024 - Castro Calva, Leila Yomary (2024)
The main objective of this Curricular Integration Work was to analyze the relationship between the game work and the development of cognitive skills in 3 and 4-year-old children from the “Fernando Suárez Palacio” Educational Unit; this research was framed in a qualitative approach and inductive method, the design was non-experimental cross-sectional, techniques such as the interview with an interview guide instrument were used, which consisted in 5 open questions, directed to a teacher and direct observation, whose instrument was the observation sheet, with 5 items, applied to a sample of 26 children of 3 and 4 years old. The results found according to the interview and the observation sheet reveal a strong link with the development of cognitive skills in children as children regularly participate in work game activities showing an easier greater to process information and learn. It was determined that children demonstrate an adequate capacity for concentration, creativity and problem solving, reflecting good cognitive development; however, a smaller number of children always present difficulties in these aspects. It is concluded that the methodology of game work applied regularly contributes positively to the cognitive development of children at this stage of their growth, aligning with the Froebel and Piaget theory. In addition, playful activities not only stimulate children's participation, but also contribute to their ability to concentrate and solve problems. Cognitive skills manifest in the ability to stay focused on tasks and overcome challenges, this also promotes their creativity and ability to interact positively. Keywords: ability, playful, concentration, resolution, growth.